Bryophyte Diversity in Mount Prau, Blumah Village, Central Java - Lianah Lianah; Niken Kusumarini; Fitriana Rochmah; Fadla Orsida; Mukhlisi Mukhlisi; Milya Ulfa Ahmad; Ainun Nadhifah (UIN Sunan Gunung Djati Bandung, 2021)
Bryophytes are a major component of the ecosystem in Indonesia. Due to their sensitiveness, the abundance and diversity of bryophytes in an ecosystem are influenced by environmental conditions. This study aimed to determine the diversity of bryophytes based on ecological parameters in the village of Blumah Kecaman Plantungan, Kendal Regency which is directly adjacent to the Mount Prau protected forest, Central Java. The data collection method used was the exploratory method and the descriptive exploratory method with survey techniques. Observation was carried out by exploring an area of 3 kilometers, every 1 km distance. An observation station was made consisting of station 1 Jiwan hamlet, station 2 Garung, and station 3 at Cengkek and Gondan springs. The specimens were identified based on taxonomic literature. Each species was collected as a specimen for further identification in the laboratory. Abiotic environment parameters such as temperature, humidity, altitude, light intensity, pH and slope were observed. The results showed that Blumah village still has high plant diversity, especially bryophytes. The more humid, the higher the place, the lower the temperature and light intensity, the more species diversity. Based on the identification results, 21 species were recorded, which includes 15 species of mosses, 4 species of liverworts, and 2 species of hornworts. The index value of bryophyte species diversity was in the medium category, and the index value of species richness and species dominance were at low levels.